Charged Si9 Clusters in Neat Solids and the Detection of [H2Si9]2− in Solution: A Combined NMR, Raman, Mass Spectrometric, and Quantum Chemical Investigation. Issue 39 (6th August 2018) - Schiegerl, Lorenz J.; Karttunen, Antti J.; Tillmann, Jan; Geier, Sebastian; Raudaschl‐Sieber, Gabriele; Waibel, Markus; Fässler, Thomas F.
Abstract: Polyanionic silicon clusters are provided by the Zintl phases K4 Si4, comprising [Si4 ] 4− units, and K12 Si17, consisting of [Si4 ] 4− and [Si9 ] 4− clusters. A combination of solid‐state MAS‐NMR, solution NMR, and Raman spectroscopy, electrospray ionization mass spectrometry, and quantum‐chemical investigations was used to investigate four‐ and nine‐atomic silicon Zintl clusters in neat solids and solution. The results were compared to 29 Si isotope‐enriched samples. 29 Si‐MAS NMR and Raman shifts of the phase‐pure solids K4 Si4 and K12 Si17 were interpreted by quantum‐chemical calculations. Extraction of [Si9 ] 4− clusters from K12 Si17 with liquid ammonia/222crypt and their transfer to pyridine yields in a red solid containing Si9 clusters. This compound was characterized by elemental and EDX analyses and 29 Si‐MAS NMR and Raman spectroscopy. Charged Si9 clusters were detected by 29 Si NMR in solution. 29 Si and 1 H NMR spectra reveal the presence of the [H2 Si9 ] 2− cluster anion in solution. Abstract : Polyanionic silicon clusters are provided by the Zintl phases K4 Si4, comprising [Si4 ] 4− units, and K12 Si17, consisting of [Si4 ] 4− and [Si9 ] 4− clusters. Charged Si9 clusters were detected for the first time by 29 Si NMR spectroscopy in the solid state and in solution. 29 Si and 1 H NMR spectra reveal the [H2 Si9 ] 2− cluster anion in solution and J ( 29 Si— 1 H) coupling shows these is proton scrambling.